International Noise Awareness Day - INAD Brazil 2023 - Kuniyoshi, Isabel Cristiane; Fonseca, William D'Andrea; Mello, Felipe Ramos de (Acústica e Vibrações, 2023)
This paper recounts Brazil's 2023 campaign, whose slogan was "Noise in communication? No connection!". The text begins with an introduction to INAD and its context in Brazil, followed by a detailed description of the theme and motto. It also discusses the development of promotional materials and describes the various activities carried out in 2023, culminating in the event's symbolic day, April 26. INAD Brazil, the national arm of the International Noise Awareness Day (INAD) campaign, is dedicated to raising awareness in society about the adverse impacts of noise on health and everyday life. Each year, INAD Brazil highlights a theme and a motto to emphasize the importance of awareness and measures to mitigate the effects of noise in our reality. Noise pollution is a global problem, causing serious damage to human health and the environment. The article concludes with ideas for the organization of INAD 2024.